ANALISIS PRINSIP BAGI HASIL DALAM PEMBIAYAAN AL.MUSYARAKAH SIRKATUL MILK UNTUK PEMBIAYAAN HUNIAN SYARIAH D! BANK MUAMMALAT INDONESIA - , Satria Adi Putra, Destri Budi Nugraheni, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of the study is to determine the practice of Al-Musyarakah Sirkatul Milk financing and the estimation of benefit sharing on the financing agreement in Al-Musyarakah Sirkatul Milk scheme in Bank Muammalat Indonesia. The research is conducted as empirical juridical with qualitative method and descriptive analytical type of study. Sampling method used in the research is purposive sampling with Sharia Complience Department Head and financing costumers as respondents. Primary data are retrieved from interview with the respondents, whereas secondary data are retrieved from Al-Musyarakah Sirkatul Milk financing agreement and previous studiesâ relevant results. Data retrieved from this study will be analyzed with qualitative method. In conclusion, based on the study the practice of islamic occupancy Al Sirkatul Milk financing in Bank Muammalat Indonesia has complied with the National Sharia Boardâs Regulation Number: 73/DSN-MUI/XI/2008 date of 14 November 2008 regarding Musyarakah Muntanaqisah. In relation to the benefit sharing estimations, can be determined as follows: (i) the lease value paid by the customers is revenue shared between the customers and the Bank in accordance with the profit sharing ratio